Potential use of agroindustrial waste as a source of phenolic compounds with biological activity - Anahí Belén Bonilla Rodríguez; Mary Mishell Pintag Fuertes; Gerardo Emilio Medina Ramírez (Medisur)
Phenolic compounds have bioactive properties of interest in Medicine. Current research focuses on the search for new sources of this type of compounds. Several studies have proposed recovering, characterizing and identifying phenolic compounds from agroindustrial waste, searching for various biological activities in them. The present research was developed with the objective of describing the potential use of agroindustrial waste as a source of phenolic compounds with biological activity and their use in Medicine. Agroindustrial waste has a high potential as a novel source of phenolic compounds with biological activity, which can be used in the pharmaceutical, food and cosmetic industries. Among its applications are antioxidant, anti-inflammatory, antimicrobial and antiproliferative activity. Several of the agroindustrial waste come from cultivable products in Ecuador, hence it constitutes an opportunity to be exploited in the national industry. Studies in Ecuador on the use of agroindustrial waste focus on obtaining biofuels, bioplastics and animal feed products, so the search for bioactive compounds from new sources is still an incipient field.